Effectiveness of Betel Leaf Extract (Piper betle L.) as a Disinfectant on Embryo Mortality, Hatchability, and Hatching Weight of Kampong Chicken Eggs - Nur Santy Asminaya; Astriana Napirah; Fuji Astuti Auza; Nurfianti Nurfianti (Pascasarjana Universitas Sulawesi Tenggara, 2023)
The process of hatching eggs is greatly influenced by the level of cleanliness of the eggs, so disinfection is carried out to reduce contamination of the eggs. However, generally, the disinfectants used are chemical-based, causing residue. This study aims to determine the effectiveness of using betel leaf extract disinfectant (Piper betle L.) on embryo mortality, hatchability, and hatching weight of village chickens. This study used a completely randomized (CRD) design with four treatments and replications. Treatments consisted of P0 (dipping solution without betel leaf extract), P1 (dipping solution containing 10% betel leaf extract), P2 (dipping solution containing 20% betel leaf extract) and P3 (dipping solution containing 30% betel leaf extract ). The data were analyzed using analysis of variance and continued with further tests of the Honestly Significant Difference Test (BNJ) on treatments that showed significant differences. The research showed that using betel leaf extract as a disinfectant of up to 30% did not significantly affect embryo mortality, hatchability, and hatching weight of kampong chicken eggs. Embryo mortality, hatchability, and hatching weight of native chickens in this study ranged between 30-45%, 55-70%, and 32.31-32.84%. The conclusion can be drawn is that using betel leaf extract up to 30% is not effective as a natural disinfectant for hatching kampong chicken eggs.